Implementasi Algoritma Zhu-Takaoka Untuk Pencarian Nama Obat Pada Aplikasi Katalog Obat Berbasis Android - Sony Sony (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Medicine is an object that is currently needed by humans, there are many names of drugs with different benefits, making it difficult for many people to find information on the name of the drug and the benefits of the drug. Technology is needed to make it easier for someone to find information on drug names and the benefits of the drug, therefore the author will build an android-based drug catalog application. With this android-based drug catalog application users can easily search for drug names by entering the name of the drug to be searched in the search table, after which the name of the drug with the benefits of the drug will appear.